BULLINGNING KICHIK MAKTAB YOSHIDAGI BOLALAR PSIXOLOGIYASIGA TA’SIRI - Berdiyeva, G.J. (SCIENCE and SOCIETY, 2025)
This article examines the psychological characteristics of bullying among primary school-aged children, the factors influencing its formation, and its key effects on children’s psychology. The emotional, personal, and social consequences of bullying are analyzed, and strategies for its prevention and mitigation are developed. This study proposes practical approaches aimed at ensuring the socio-psychological well-being of children.